2001
DOI: 10.1007/s005200100251
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and treatment of cancer-related fluid deficits: volume depletion and dehydration

Abstract: Fluid deficits should be divided into two categories (dehydration and volume depletion) according to pathophysiology and into 3 categories (hyponatremic, hypernatremic, and isotonic) according to the plasma sodium concentration. Dehydration (total water deficit especially intracellular) is always hypernatremic, while volume depletion (intravascular water and sodium deficit) is either hyponatremic, hypernatremic, or isotonic. There are no clear clinical differences among the various categories, but a delay of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 92 publications
0
33
0
1
Order By: Relevance
“…The general use of the term 'dehydration' to mean volume depletion and hypovolemia as well is erroneous, even though each of these is also associated with a fluid deficit state [60,63,92]. Dehydration refers specifically to a deficit in total body water, which affects the intracellular and interstitial spaces.…”
Section: Fluid Deficit State: Pathophysiology and Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…The general use of the term 'dehydration' to mean volume depletion and hypovolemia as well is erroneous, even though each of these is also associated with a fluid deficit state [60,63,92]. Dehydration refers specifically to a deficit in total body water, which affects the intracellular and interstitial spaces.…”
Section: Fluid Deficit State: Pathophysiology and Pathogenesismentioning
confidence: 99%
“…The high risk of fluid deficit in this population is well recognized [21,47,53,94,108], especially in the presence of one or more of the factors listed in Table 3. Even the process of water restriction prior to laboratory procedures has been suggested as a risk factor [92]. A study of elderly patients suggested that female gender, age over 85 years old, presence of more than four chronic medical conditions or acute diagnoses, use of more than four medications, use of laxatives, and bedridden status were all associated with biochemical markers of fluid deficit (sodium levels greater than 150 mmol/l, or blood urea nitrogen/creatinine ratio greater than 25) [53].…”
Section: Fluid Deficit State: Pathophysiology and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these issues remain a room for debates. Physicians are still confused when they are faced with this problem [13][14][15][16][17][18]. For example, according to the study of Tatsuya Marita et al [19], 72% of Japanese physicians believe that it is difficult to adequately determine the medical indications for intravenous hydration.…”
Section: Introductionmentioning
confidence: 99%
“…Many patients with cancer do not fit this physiological pattern (healthy individual phenotype). On the contrary, most patients with cancer suffer from hyponatremia rather than hypernatremia, due to low sodium and serum osmolality (Sarhill et al, 2001;Davis et al, 2009;Nwosu et al, 2013). In many instances, the cancer is accompanied by the syndrome of inappropriate antidiuresis (SIADH).…”
Section: Introductionmentioning
confidence: 99%